2018
DOI: 10.3389/fpsyg.2018.01521
|View full text |Cite
|
Sign up to set email alerts
|

Online Purchase Intention of Fruits: Antecedents in an Integrated Model Based on Technology Acceptance Model and Perceived Risk Theory

Abstract: Over recent years, online purchase platforms of fruits are increasingly emerged to advance the e-commerce development and improve quality of human life. Unfortunately, we empirically observed that a lot of enterprises selling fruits online have suffered from bankruptcy due to a lot of complicated factors, such as inefficient logistics, low acceptance of online platforms, and financial risks. One of the root causes responsible for such an unanticipated phenomenon is related to the purchase intention, which moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 29 publications
6
51
1
1
Order By: Relevance
“…OCRs (online customer reviews) can deliver signals to consumers coping with uncertainty (Lau et al, 2011;Wei et al, 2018). However, the OCR-provided signals derive from consumers' perceptions toward credibility and are independent of marketers' interests; thus, it is key to compare these with the effect of brand equity.…”
Section: Brand Equitymentioning
confidence: 99%
“…OCRs (online customer reviews) can deliver signals to consumers coping with uncertainty (Lau et al, 2011;Wei et al, 2018). However, the OCR-provided signals derive from consumers' perceptions toward credibility and are independent of marketers' interests; thus, it is key to compare these with the effect of brand equity.…”
Section: Brand Equitymentioning
confidence: 99%
“…Purchase Intention dalam penelitian ini sebagai perilaku yang timbul sebagai respon terhadap suatu objek yang menunjukan keinginan pelanggan untuk melakukan pembelian (Wei et al, 2018). Adapun Indikator purchase intention adalah sebegai berikut: Tertarik untuk mencari informasi tentang produk, Mempertimbangkan untuk membeli, Tertarik untuk mencoba produk, Ingin memiliki produk.…”
Section: Tabel 1 Data Penjualan Specsunclassified
“…From a customer's perspective, a price concession brings economic benefits to him/her, thereby stimulating his/her positive emotions and increasing the willingness to buy [39][40][41]. Wei et al [42] found that price concession has a positive impact on consumer purchase intention in fruit-related e-commerce. In line with their definition [42], we define price concession in the context of crowdfunding products/services as the extent to which buying crowdfunding products/services can save customers money compared with buying counterparts or substitutes in other channels, including offline channels such brick-and-mortar stores and non-crowdfunding online channels such as traditional e-commerce websites.…”
Section: Perceived Benefitsmentioning
confidence: 99%
“…Wei et al [42] found that price concession has a positive impact on consumer purchase intention in fruit-related e-commerce. In line with their definition [42], we define price concession in the context of crowdfunding products/services as the extent to which buying crowdfunding products/services can save customers money compared with buying counterparts or substitutes in other channels, including offline channels such brick-and-mortar stores and non-crowdfunding online channels such as traditional e-commerce websites. An empirical study on a crowdfunding website revealed that a project's clear discount information is positively related to the total amount of funds finally collected [43].…”
Section: Perceived Benefitsmentioning
confidence: 99%
See 1 more Smart Citation